The works of Thomas Traherne. or, Divine morallity, opening the way to blessedness, by the rules of vertue and reason : Roman forgeries : or, A true account of false records discovering the impostures and counterfeit antiquities of the Church of Rome - Traherne, Thomas, -1674 (D.S. Brewer, 2022)
Hereford Cathedral is proud of its four stained-glass windows commemorating Traherne, but these volumes are as glorious a memorial. DAILY TELEGRAPH [Christopher Howse].